Information Technology Students’ Insights from Their On-The-Job Training: Input to an Internship Manual - Casugay, Jake Vincent R.; Cabauatan, Wilfred F.; Esperanza, Jeanely A.; Fontanilla, Marie Ann G.; Subang, Albert H. (Future Science / FSH-PH Publications, 2024)
This quantitative research utilizing the descriptive-survey design assessed the on-the-job training performance of the Bachelor of Science in Information Technology (BSIT) students. Ninety-four students have completed their on-the-job training in school year 2017-2018 and have participated in the study. The data were collected using a survey questionnaire and descriptively treated using frequency, percentage, and weighted mean. In addition, the qualitative part of the post-evaluation survey form was treated using thematic analysis. The study revealed the following: the partner-company organization is related to the student’s specialization as they utilized IT-based software and assigned tasks related to information technology. Student trainees were able to develop their communication skills while mobile application development skills were identified as the least. OJT students also identified Professional Ethics and Values Education for IT, Multimedia Systems, Operating Systems as well as Oral Communication, Fundamentals of Grammar, and Presentation Skills and Technical Writing as the most relevant subject courses; and they perceived doing work not related to information technology, extended OJT, overtime, and certain provision of existing manual as problems. The researchers concluded that the BSIT Internship manual when implemented can effectively improve their field work performance